The Effect Of Financial Literacy On The Lifestyle Of Gen-Z Accounting Students Unismuh Makassar - Sitti Syaharana; Muryani Arsal; Hasanuddin , Hasanuddin (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to examine the influence of financial literacy on the lifestyle of Gen-Z Unismuh Makassar accounting students. This research uses quantitative methods. The sample in this study took 2020 Accounting Students from the Faculty of Economics and Business, Muhammadiyah University of Makassar.This research data was obtained from a questionnaire (primary data). The research results from data processed using SPSS 26 statistical calculations. Based on the partial SPSS 26 output results, the financial literacy research results obtained a tcount of 5.145 while the ttable was 1.995, meaning that t_count was 5.145 > t_table 1.995. This indicates that financial literacy has a positive and significant influence on the lifestyle of Gen-Z Accounting Students. The suggestion from this research is for Accounting Students at the Faculty of Economics and Business, Muhammadiyah University of Makassar to further improve their understanding and abilities in Financial Literacy towards their limited lifestyle so that it is better and for future researchers it is hoped that they can add other indicators and variables.